Clinical and biochemical profile of iron deficiency state in preanemic under 5 children in a tertiary care hospital - N. S., Chithambaram; S., Radha Reddy (International Journal of Contemporary Pediatrics, 2017)
Background: Anemia is a global public health problem affecting both developing and developed countries with major consequences for human health as well as social and economic development. The aim was to identify iron deficiency state early before developing anemia and to analyze the clinical finding with iron deficiency state. Methods: Cross sectional study was done at Vydehi Institute of Medical Sciences and Research Centre, Bangalore, India. 100 children between 6 month to 5 years of age with normal haemoglobin were studied for iron deficiency state. After taking informed consent a detailed history and clinical examination was taken. In those children with normal Hb, investigations like serum ferritin, serum iron and transferrin saturation were done to diagnose the iron deficiency state. Results: Out of 100 children in the study, mean hemoglobin was 11.8 gm/dl, the mean serum ferritin level was 59.1ng/ml and transferrin saturation was 18.77%. The overall prevalence of iron deficiency in this study based on low serum ferritin was 16% and low transferrin saturation was 51%. 7 children has low DQ out of which 3 were ADHD, 2 had hyperactivity and 2 with learning problem. Among them one child has low ferritin and 5 had low transferrin saturation. Conclusions: Iron deficiency is an important public health problem. The findings in this study are consistent compared to other studies. Therefore, prompt screening for iron deficiency, even in non-anemic under five children in developing countries should be encouraged. If evaluation of iron status is done only by Hb early signs of iron depletion can go undetected. By monitoring the status of storage iron(ferritin), we can detect iron deficiency state earlier and initiate appropriate treatment to prevent IDA.